Representing Indian Agricultural Practices and Paddy Cultivation in the Variable Infiltration Capacity Model - Jisha Joseph; Subimal Ghosh (Water Resources Research, 2023)
Abstract Increased irrigation due to agricultural intensification has profound impacts on the surface water and energy balance at regional to local scales. Recent updates of the state‐of‐the‐art Land Surface Models (LSMs) include the impacts of irrigation on surface hydrology. The Indo‐Gangetic Plain (IGP) is one of the global hotspots of irrigation water applications. However, the direct application of these models to Indian basins has certain limitations. The commonly employed flood irrigation technique is often indiscriminate and unmanaged, unlike the state‐of‐the‐art models' estimation of crop water use based on soil moisture (SM) conditions. The primary crop in the IGP is paddy, cultivated in inundated fields with quite distinct water and energy partitioning mechanisms represented in very few models. Here, we developed an improved irrigation module to simulate the Indian agricultural practices for the widely used Variable Infiltration Capacity model. We incorporated the crop‐specific water use for flood irrigation, calculated based on previously reported field studies. The water and energy balance processes are modified by incorporating the ponded paddy fields with proper parameterization. We achieved moderate improvement in the simulated evapotranspiration (ET) and SM of the IGP, particularly in the non‐monsoon seasons with the updated model. We found that ET and SM are more sensitive to the irrigation techniques than the interval of irrigation application. Runoff strongly responded to irrigation technique as well as the interval of application. We emphasize accurate representation of irrigation practices in the LSMs, specifically when applied to the human‐natural hydrological system.